The Determinants of Technical Efficiency of Oil Palm Smallholders in Indonesia - Varina, Firna; Hartoyo, Sri; Kusnadi, Nunung; Rifin, Amzul (International Journal of Economics and Financial Issues, 2020)
The main objective of the present study is to analyze the technical efficiency (TE) and evaluate its determinant in smallholder oil palm farming in Indonesia. The stochastic frontier analysis was applied to 20,409 selected oil palm farmers from the results of the 2014 Estate Cultivation Household Survey (ST2013 SKB) conducted by BPS-Statistics Indonesia. The results showed that all the input variables had a positive influence on oil palm production along with existing inefficiencies among heterogeneous smallholder farmers. They also indicated that the mean level of the TE among oil palm smallholders was 0.6694. Furthermore, variables such as farmer age, education, type of farmer, and location of the farm had positive and significant effects on TE. Therefore, the development policies in the oil palm smallholder sector might focus on promoting education and facilitate the accessibility of farmers to extension services by giving guidance on farming management based on environmentally friendly principles to improve production regarding land expansion. Keywords: smallholder, stochastic frontier, technical efficiency JEL Classifications: C51, D24, Q15 DOI: https://doi.org/10.32479/ijefi.10594